The Impact of SIX SIGMA DMAIC Methodology in the Effective Pharmacy Inventory Management System in a Major Trauma Care Center – A Prospective Observational Study - Lourdu, Britto Duraisingh; Theivasigamani, Kumutha; Harwin, Anagha; Paulraj, Kensylin; Paul, Sandra; Lachmanan, Akash (Indian Journal of Pharmacy Practice)
Objectives: Define the defects in the inventory management process to identify the opportunities with high potential for improvement and also to measure the identified errors and quantify them to obtain statistical and graphical data. Materials and Methods: The study was conducted in the department of pharmacy in a major trauma care center in Tamil Nadu, India for Six months by using SIX SIGMA DMAIC TOOL. The study was conducted in the four major pharmacy management system units of the trauma care center which included the store, pharmacy, infirmary unit, and return medication counter. Results: The impact of inventory management was analyzed, where we observed changes in sigma value which eventually visualized the improvisation in inventory management system. Conclusion: We could conclude that, use of six sigma DMAIC methodology reduced the number of errors from procurement facets, distribution facets, infirmary unit facets, and return medicine unit in the major trauma care center.
Keywords: Inventory management; Six Sigma; Pharmacy; Errors; Improve; DMAIC; Procurement; distribution; Infirmary; supply chain management; Discrepancies